APPLICATION OF JIGSAW COOPERATIVE LEARNING MODEL TO INCREASE STUDENT LEARNING OUTCOMES IN ENGINEERING MECHANICAL LESSON - Envilwan Berkat Harefa (UNIVERSITAS NEGERI MEDAN, 2021)
The problem in this study is the Jigsaw Cooperative learning model has not been applied optimally to engineering mechanics subjects and student learning outcomes do not meet the KKM standard of 70. The objectives of the study: (1) to describe the learning process in engineering mechanics subjects by applying cooperative learning models Jigsaw Type in Vocational Schools, and (2) To find out student learning outcomes in Mechanical Engineering subjects, especially in Basic Competence, apply how to arrange an equivalent style in building structures by applying the Jigsaw Type cooperative learning model in Vocational Schools This type of research is Classroom Action Research (CAR). This research was carried out in SMK with the research subjects of Class X students. The instruments in this study were observation sheets of the learning process, (teachers' respondents), student activity observation sheets, photo documentation, and learning outcomes tests. With the data analysis technique, the observation sheet was processed with a Likert scale and the learning outcomes test was carried out with a validation test and a feasibility test. The results of the study: (1) In the first (first) cycle the average percentage of observations in the learning process (teacher respondents) was 65%, while in the second (two) cycle the average percentage of observations in the learning process (teacher respondents) was 85, 37%. (2) In the first (first) cycle, the average percentage of observation of student activity, which is 34.62%, has not reached the target set, while in cycle II (two) the average percentage of observation of student activity, which is 88.46%, has reached the target. set at 70%. (3) In the first (first) cycle, the average count of student learning outcomes is 60.82, the percentage value of student completeness is 30.77%, while in the second (second) cycle, the average student learning outcome is 82.18 classified as good. , and the percentage value of student learning outcomes completeness 92.31% has reached the target set, namely 70. From the research findings above, it can be concluded that by applying the Jigsaw Type cooperative learning model to engineering mechanics subjects, it can improve student learning outcomes